More than half of front-line healthcare workers unknowingly used an N95/P2 mask without adequate airborne protection: An audit in a tertiary institution. Issue 5 (September 2021) - Regli, Adrian; Thalayasingam, Priya; Bell, Emily; Sommerfield, Aine; von Ungern-Sternberg, Britta S
: Front-line staff routinely exposed to aerosol-generating procedures are at a particularly high risk of transmission of severe acute respiratory syndrome coronavirus 2. We aimed to assess the adequacy of respiratory protection provided by available N95/P2 masks to staff routinely exposed to aerosol-generating procedures. We performed a prospective audit of fit-testing results. A convenience sample of staff from the Department of Anaesthesia and Pain Medicine, who opted to undergo qualitative and/or quantitative fit-testing of N95/P2 masks was included. Fit-testing was performed following standard guidelines including a fit-check. We recorded the type and size of mask, pass or failure and duration of fit-testing. Staff completed a short questionnaire on previous N95/P2 mask training regarding confidence and knowledge gained through fit-testing. The first fit-pass rate using routinely available N95/P2 masks at this institution was only 47%. Fit-pass rates increased by testing different types and sizes of masks. Confidence 'that the available mask will provide adequate fit' was higher after fit-testing compared with before fit-testing; (median, interquartile range) five-point Likert-scale (4.0 (4.0–5.0) versus 3.0 (2.0–4.0); P <0.001). This audit highlights that without fit-testing over 50% of healthcare workers were using an N95/P2 mask that provided insufficient airborne protection. This high unnoticed prevalence of unfit masks among healthcare workers can create a potentially hazardous false sense of security. However, fit-testing of different masks not only improved airborne protection provided to healthcare workers but also increased their confidence around mask protection.